Effects of Peptide on NK Cell-Mediated MHC I Recognition - Khakoo, Salim I.; Cassidy, Sorcha; Cheent, Kuldeep (Frontiers in Immunology, 2014)
The inhibitory receptors for MHC class I have a central role in controlling NK cell activity. Soon after their discovery it was found that these receptors have a degree of peptide selectivity. Such peptide selectivity has been demonstrated for all inhibitory KIR tested to date, certain activating KIR, and also members of the C-type lectin-like family of receptors. This selectivity is much broader than the peptide specificity of T cell receptors, with NK cell receptors recognizing peptide motifs, rather than individual peptides. Inhibitory receptors on NK cells can survey the peptide:MHC complexes expressed on the surface of target cells, therefore subsequent transduction of an inhibitory signal depends on the overall peptide content of these MHC class I complexes. Functionally, KIR-expressing NK cells have been shown to be unexpectedly sensitive to changes in the peptide content of MHC class I, as peptide:MHC class I complexes that weakly engage KIR can antagonize the inhibitory signals generated by engagement of stronger KIR-binding peptide:MHC class I complexes. This property provides KIR-expressing NK cells with the potential to recognize changes in the peptide:MHC class I repertoire, which may occur during viral infections and tumorigenesis. By contrast, in the presence of HLA class I leader peptides, virus-derived peptides can induce a synergistic inhibition of CD94:NKG2A-expressing NK cells through recruitment of CD94 in the absence of NKG2A. On the other hand CD94:NKG2A-positive NK cells can be exquisitely sensitive to changes in the levels of MHC class I. Peptide antagonism and sensitivity to changes in MHC class I levels are properties that distinguish KIR and CD94:NKG2A. The subtle difference in the properties of NK cells expressing these receptors provides a rationale for having complementary inhibitory receptor systems for MHC Class I.